The Effect of Headquarter Integration Mechanisms on Subsidiaries’ New Product Success: From Control to Coordination Mechanism - Firmanzah, Firmanzah (The South East Asian Journal of Management, 2007)
New product launching (NPL) to the local market by subsidiary managers is a strategic activity, which requires organizational supports from MNC global network. The NPL activity is marked by high level of uncertainty, risk, and market failure. Thus, a headquarter needs to integrate the subsidiary NPL into global strategy. There are two mechanisms to integrate subsidiaries’ activities during NPL process; coordination and control process. By testing the effect of each mechanism on role clarity and functional conflict, I found that coordination mechanism increase role clarity between headquarter and subsidiaries’ managers. In contrast, exercising control mechanism reduces role clarity and functional conflict between headquarter and subsidiaries’ managers during NPL. This research shows that both role clarity and functional conflict increase new product commercial performance introduced by subsidiary in the local market.